Unraveling reaction mechanisms by means of Quantum Chemical Topology Analysis. Issue 19 (14th March 2014) - Andrés, Juan; González‐Navarrete, Patricio; Safont, Vicent Sixte; Hernández‐Laguna, Alfonso; Sainz‐Díaz, Claro Ignacio
<x xml:space="preserve">Abstract</x> A chemical reaction can be understood in terms of geometrical changes of the molecular structures and reordering of the electronic densities involved in the process; therefore, identifying structural and electronic density changes taking place along the reaction coordinate renders valuable information on reaction mechanism. Understanding the atomic rearrangements that occur during chemical reactions is of great importance, and this perspective aims to highlight the major developments in quantum chemical topology analysis, based on the combination of electron localization function and catastrophe theory as useful tools in elucidating the bonding and reactivity patterns of molecules. It reveals all the expected, but still ambiguous, elements of electronic structure extensively used by chemists. The chemical bonds determine chemical reactivity, and this technique offers the possibility of their visualization, allowing chemists to understand how atoms bond, how and where bonds are broken/formed along a given reaction pathway at a most fundamental level, and so, better following and understanding the changes in the bond pattern. Their results clearly herald a new era, in which the atomic imaging of chemical bonds will constitute a new method for examining chemical structures and reaction mechanisms. The important feature of this procedure is that in practice the scope of its values is system‐independent. In addition, from a practical point of view, it is cheap to calculate and implement because wave functions are the required input, which are easily available from standard calculations. To capture these results two reaction mechanisms: isomerization of C(BH)2 carbene and the thermal cycloheptatriene‐norcaradiene isomerizations have been selected, indicating both the generality and utility of this type of analysis. © 2014 Wiley Periodicals, Inc.